Volume 2: Combustion, Fuels and Emissions, Parts a and B 2012
DOI: 10.1115/gt2012-69357
|View full text |Cite
|
Sign up to set email alerts
|

Study of Fuel Composition Effects on Flashback Using a Confined Jet Flame Burner

Abstract: Flashback is the main operability issue associated with converting lean, premixed combustion systems from operation on natural gas to operation on high hydrogen content fuels. Most syngas fuels contain some amount of hydrogen (15–100%) depending on the fuel processing scheme. With this variability in the composition of syngas, the question of how fuel composition impacts flashback propensity arises. To address this question, a jet burner configuration was used to develop systematic data for a wide range of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Since research on flashback began with the first systematic study by Lewis and von Elbe [1,2], the focus has been on measuring flashback limits in (non-swirling) Bunsen-flame type burners for many years [3][4][5][6][7], including more recent studies carefully testing additional parameters such as confinement, wall temperature and pressure [8][9][10][11][12][13]. High-speed optical diagnostics and advanced simulation tools have been applied more recently to reveal new information about the flame propagation dynamics [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Since research on flashback began with the first systematic study by Lewis and von Elbe [1,2], the focus has been on measuring flashback limits in (non-swirling) Bunsen-flame type burners for many years [3][4][5][6][7], including more recent studies carefully testing additional parameters such as confinement, wall temperature and pressure [8][9][10][11][12][13]. High-speed optical diagnostics and advanced simulation tools have been applied more recently to reveal new information about the flame propagation dynamics [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the laminar case, it is found that the turbulent flashback takes place at a considerably higher average velocity than that prescribed by the gradient principle [5]. In other words, the critical velocity gradients at flashback are significantly increased when the flow conditions are changed from laminar to turbulent [6][7][8][9][10]. Accordingly, the increase in the critical velocity gradient may be attributed to the decreased penetration distance, the increased burning velocity, or the combined effect of both.…”
Section: Introductionmentioning
confidence: 64%
“…To be compatible with the procedure for the H 2 -rich mixtures, the properties of the syngas flames were evaluated based on the same reaction scheme [34]. Note that since the flashback behavior was considered to be still dominated by the hydrogen content [10,16,17], the Lewis number was again evaluated by dividing the mixture thermal diffusivity with the ordinary multicomponent diffusion coefficient for the H 2 -N 2 pair.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations